2019
DOI: 10.1371/journal.pone.0210969
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome among residents of Mizan-Aman town, South West Ethiopia, 2017: A cross sectional study

Abstract: IntroductionGlobally, it is estimated that around 20–25% adult population has metabolic syndrome. Individuals who have metabolic syndrome are up to five times more susceptible for chronic diseases than those who have no metabolic syndrome. In Ethiopia there is no sufficient information regarding the magnitude and factors of metabolic syndrome. The aim of this study is to assess prevalence and associated factors of metabolic syndrome among residents of Mizan-Aman town, South West, Ethiopia.MethodsThe community … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
17
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 22 publications
7
17
3
Order By: Relevance
“…This was quite similar to a crossectional study from residents of Mizan-Aman town, South West Ethiopia, in which individuals with the educational status of below degree are up to 89% protective to develop MS than those with the educational status of degree and above. 33 This finding correspondingly align with the studies from Kenya (Kiama, 2018 and Kaduk, 2012). 32,34 This confirms that education is a key to open any locked secrets of life in the world that enable everybody to have a standardized and healthy lifestyle by getting a behavioral change.…”
Section: Discussionsupporting
confidence: 85%
“…This was quite similar to a crossectional study from residents of Mizan-Aman town, South West Ethiopia, in which individuals with the educational status of below degree are up to 89% protective to develop MS than those with the educational status of degree and above. 33 This finding correspondingly align with the studies from Kenya (Kiama, 2018 and Kaduk, 2012). 32,34 This confirms that education is a key to open any locked secrets of life in the world that enable everybody to have a standardized and healthy lifestyle by getting a behavioral change.…”
Section: Discussionsupporting
confidence: 85%
“…The prevalence of MetS in this study was 21.8%, which was higher than previously reported prevalences from urban areas of Ethiopia like Mizan Aman town (9.6%) [26], and at a national level (11.7%) [15]. Since the study was conducted among healthy adult individuals, this prevalence was considered high.…”
Section: Discussioncontrasting
confidence: 63%
“…This could be due to decreased activity level; physiological changes like increased fat mass accompanied by decreased muscle mass; and increased alcohol consumption. A similar finding has been reported from Mizan Aman town in Southern Ethiopia, with a risk of MetS was lower among lower age groups[26]. A study conducted in Addis Ababa also found that the prevalence of MetS increased with age, with the highest prevalence reported among 45-54years old adults[22].…”
supporting
confidence: 77%
“…The magnitude of MetS in the present study was 21.8%, which was higher than previously documented findings from some urban areas of Ethiopia like Addis Ababa (17.9%). 20 , 27 , 37 The difference may be due to variation in sample size, level of urbanization, and study period. Besides, since the study was carried out in the second-largest city in Ethiopia, residents may have better economic status, which may contribute to a dietary shift (from fiber-rich traditional foods to refined and processed foods).…”
Section: Discussionmentioning
confidence: 99%